Pelatihan Budgeting sebagai Strategi Penguatan Kapasitas Finansial bagi Pekerja Migran Indonesia di Singapura - Agustinus Winoto (Jurnal Abdi Masyarakat Nusantara, 2025)
Indonesia, being one of the most populous nations globally, has dispatched a considerable amount of its workforce overseas, commonly referred to as Indonesian Migrant Workers (PMI). These workers significantly contribute to the Indonesian economy by the consistent remittances they transmit to their relatives domestically. Nonetheless, numerous migrant workers continue to possess an inadequate comprehension of effective financial administration, encompassing financial planning during their residence in Singapore and the attainment of long-term objectives in Indonesia. This community engagement program aims to enhance the financial literacy of migrant workers. The implementation technique involves direct lectures in Singapore addressing various critical issues, including fundamental budgeting ideas and the simulation of monthly spending while residing in Singapore. The results of this exercise demonstrate that an increasing percentage of Indonesian migrant workers have attained a superior comprehension of financial management. They may now build comprehensive budgets for their living expenses and remittances to Indonesia in a more organized fashion. Moreover, they have acquired the assurance to contemplate long-term goals through the financial resources at their disposal. Consequently, this financial literacy lecture program is considered essential for extension and implementation in other countries with a presence of Indonesian migrant workers.